Determinasi Return Saham : Peran Struktur Modal dan Nilai Perusahaan - Mayang Murni; Dinda Hafidzoh; Ulfa Utari (UNIVERSITAS DHARMAWANGSA, 2026)
This study aims to analyze the impact of capital structure and firm value on stock returns for telecommunications companies listed on the Indonesia Stock Exchange during the 2014–2023 period. The research background is based on the rapid growth of the telecommunications industry in the digital era, which has not always been accompanied by improved stock performance, as seen in the cases of Telkom Indonesia (TLKM) and Indosat Ooredoo Hutchison (ISAT), as well as the inconsistency of previous research findings. This study employs a quantitative descriptive approach using secondary data, purposive sampling, and descriptive statistical analysis along with multiple linear regression. The results indicate that, individually, capital structure and firm value have a positive and significant impact on stock returns, and collectively, capital structure and firm value have a significant impact on stock returns. These findings indicate that financing decisions and market perceptions of firm value are important factors in determining stock returns, and thus should be considered by investors and companies in their decision-making.